Immune-related gene risk score predicting the effect of immunotherapy and prognosis in bladder cancer patients - Zou, Yuantao; Yuan, Gangjun; Tan, Xingliang; Luo, Sihao; Yang, Cong; Tang, Yi; Wang, Yanjun; Yao, Kai (Frontiers in Genetics, 2022)
Immune checkpoint inhibitor therapy has changed the treatment model of metastatic bladder cancer. However, only approximately 20% of patients benefit from this therapy, and robust biomarkers to predict the effect of immunotherapy are still lacking. In this study, we aimed to investigate whether immune-related genes could be indicators for the prognosis of bladder cancer patients and the effect of immunotherapy. Based on the bladder cancer dataset from the Cancer Genome Atlas (TCGA) and GSE48075, 22 immune microenvironment-related cells were identified by CIBERSORT. After performing a series of bioinformatic and machine learning approaches, we identified distinct tumor microenvironment clusters and three bladder cancer-specific immune-related genes (EGFR, OAS1, and MST1R). Then, we constructed an immune-related gene risk score (IRGRS) by using the Cox regression method and validated it with the IMvigor210 dataset. Afterward, the molecular and immune characteristics and prognosis of IRGRS-defined subgroups were analyzed. IRGRS-high patients had a worse overall survival than IRGRS-low patients, which was consistent with the result in the IMvigor210 dataset. Comprehensive analysis shows that patients with high IRGRS scores are mainly enriched in basal/squamous type (Ba/Sq), and tumor metabolism-related pathways are more Active, with higher TP53 and RB1 gene mutation rates, lower CD4+/CD8+ T cell infiltration, higher M0 macrophage infiltration, and lower immunotherapy efficacy. In contrast, Patients with low IRGRS scores are mainly enriched in the luminal papillary type (LumP), which is associated with the activation of IL-17 and TNF signaling pathways, higher mutation rates of FGFR3 and CDKN1A genes, higher CD4+/CD8+ T cell infiltration content and The level of M0 macrophage infiltration was relatively low, and the immunotherapy was more probably effective. Our study constructed an IRGRS for bladder cancer and clarified the immune and molecular characteristics of IRGRS-defined subgroups of bladder cancer to investigate the association between IRGRS and its potential implications for prognosis and immunotherapy.